A Grounded Theory Update on the Roswell UFO Incident - Randle, Kevin (Journal of Scientific Exploration, 2022)
Something unquestionably strange fell southeast of the tiny New Mexican town of Corona in the summer of 1947—an event that has become an iconic case in ufology and part of mainstream culture. Documentation and eyewitness testimony proves that rancher William Ware “Mack” Brazel took samples of that debris into the Roswell, New Mexico, sheriff’s office who in turn, reported the situation to Roswell Army Air Force officials. Controversy about the incident has always centered on the identification of the recovered debris versus its existence. Photographs of the purported debris have suggested a terrestrial explanation, while eyewitness descriptions have supported either that explanation or something much more exotic. Attempts to decipher text from a photographed document known as the Ramey Memo have not provided definitive results that would rule out any explanations. Still, there are two areas in which empirical studies can be conducted and advancements possibly made. These involve (a) strides to clarify the operational and logistical details of ‘Project Mogul,’ which is the US military’s claimed source of the debris, and (b) new efforts to read the Ramey Memo from higher quality digital scans. A grounded theory (or deductive) examination of these two lines of empirical evidence fails to clearly support the military’s latest ‘official explanation’ and thus leaves open the extraterrestrial hypothesis for the debris. Future directions for research are therefore discussed. Keywords: empiricism, Project Mogul, UAPs, UFOs, Roswell Incident, Ramey memo, trace cases.